Oligosaccharides from Morinda officinalis Slow the Progress of Aging Mice by Regulating the Key Microbiota-Metabolite Pairs. (19th December 2019) - Xin, Yang; Diling, Chen; Tianlu, Chen; Jun, Zhao; Xiaocui, Tang; Yinrui, Guo; Ou, Shuai; Tianming, Deng; Guoyan, Hu
Abstract : The gut microbiota is considered an important factor in the progression of Alzheimer's disease (AD). Active research on the association between the metabolome and the gut microbiome is ongoing and can provide a large amount of beneficial information about the interactions between the microbiome and the metabolome. Previous studies have shown that the oligosaccharides from Morinda officinalis (OMO) can delay the progress of AD in model animals by regulating the diversity of the gut microbiome and metabolic components, and the correlation between the gut microbiome and metabolic components still needs to be further verified. This study applied a new two-level strategy to investigate and ensure the accuracy and consistency of the results. This strategy can be used to determine the association between the gut microbiome and serum metabolome in APP/PS1 transgenic mice and C57BL/6J male mice. The " 4C0d-2 spp.-Cholesterol, " " CW040 spp.-L-valine, " " CW040 spp.-L-acetylcarnitine, " " RF39 spp.-L-valine, " " TM7-3 spp.-L-valine, " and " TM7-3 spp.-L-acetylcarnitine" associations among specific "microbiota-metabolite" pairs were further identified based on univariate and multivariate correlation analyses and functional analyses. The key relevant pairs were verified by an independent oligosaccharide intervention study, and the gut microbiome and serum metabolome of the OMO intervention group were similar to those of the normal group. The results indicate that OMO can significantly suppress Alzheimer's disease by regulating the key microbiota-metabolite pairs. Therefore, this two-level strategy is effective in identifying the principal correlations in large datasets obtained from combinations of multiomic studies and further enhancing our understanding of the correlation between the brain and gut in patients with AD.